PENGGUNAAN APLIKASI PROPROFS GAMES DALAM MENINGKATKAN EFEKTIVITAS EVALUASI PEMBELAJARAN PAI SISWA KELAS IV MATERI IMAN KEPADA RASUL ALLAH KELAS IV SD NEGERI 1 SUKOREJO - Husniah, Mahirotul; Sudirman, Sudirman; Wahyuni, Esa Nur (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This research is based on the issue of how the use of the Proprofs Games application can enhance the effectiveness of the evaluation of Islamic Religious Education (PAI) learning in fourth-grade students on the subject of belief in the Prophet Muhammad at SD Negeri 1 Sukorejo. The objective of this research is to determine how the use of the Proprofs Games application improves the effectiveness of learning evaluation for fourth-grade students on the subject of belief in the Prophet Muhammad at SD Negeri 1 Sukorejo. This research employs a classroom action research with two cycles. Each cycle consists of four stages: planning, action, observation, and reflection. The target of this research is fourth-grade students. The data obtained are from observations. The analysis results indicate that the use of the Proprofs Games application is highly effective and can provide significant results in improving the effectiveness and participation in the evaluation of PAI learning. This is evidenced by the data of students in Cycle 1 reaching 69.23%, increasing in Cycle 2 to 84.62%, and in Cycle 3 reaching 92.31%, categorized as good. Additionally, the use of the Proprofs Games application as the main tool can also enhance students' discipline in learning and their learning outcomes in completing assignments. This is evident from the average data in Cycle 1 reaching 56.35% with an average completeness of 72.22%, increasing in Cycle 2 to 73.33% with completeness of 77.27%, and further increasing in Cycle 3 to 89.38% with an average completeness of 91.67%. Therefore, the research is considered successful. Abstrak Penelitian ini berdasarkan permasalahan bagaimanakah Penggunaan Aplikasi Proprofs Games Dalam Meningatkan Efektivitas Evaluasi Pembelajaran PAI Siswa Kelas IV Materi Iman Kepada Rasul Allah SD Negeri 1 Sukorejo. Sedangkan tujuan dari penelitian ini adalah Untuk mengetahui bagaimana Penggunaan Aplikasi Proprofs Games Dalam Meningatkan Efektivitas Evaluasi Pembelajaran Siswa Kelas IV Materi Iman Kepada Rasul Allah SD Negeri 1 Sukorejo. Penelitian ini menggunakan penelitian tindakan kelas sebanyak dua siklus. Setiap siklus terdiri dari empat tahap yaitu : perencanaan, tindakan, observasi dan refleksi. Sasaran penelitian ini adalah siswa kelas IV. Data yang diperoleh berupa hasil pengamatan/observasi. Dari hasil analis didapatkan bahwa penggunaan aplikasi proprofs game sangat efektif serta dapat memberikan hasil yang signifikan dalam meningkatkan efektifitas keaktifan Evaluasi pembelajaran PAI Hal ini terbukti dari data peserta didik pada siklus 1 mencapai 69,23%, meningkat pada siklus 2 menjadi 84,62 % dan pada siklus 3 mencapai 92,31 %. sehingga dikategorikan baik. Selain itu, penggunaan Aplikasi proprofs games sebagai sarana utama juga dapat meningkatkan kedisiplinan pembelajaran dan hasil belajar peserta didik dalam mengerjakan tugas. Hal ini terbukti dari data rata-ratanya pada siklus 1 mencapai 56,35% dengan rata-rata ketuntasan 72,22%, meningkat pada siklus 2 menjadi 73,33 % dengan ketuntasan 77,27%, meningkat pada siklus 3 menjadi 89,38 % dengan ketuntasannya ratarata 91,67%, sehingga penelitian dinyatakan berhasil.